2011
DOI: 10.1007/s00540-011-1228-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided obturator nerve block: a single interfascial injection technique

Abstract: We describe a new technique of single interfascial injection for 25 patients scheduled for transurethral bladder tumor resection. An ultrasound probe was placed at the midline of inguinal crease and moved medially and caudally to visualize the fascial space between the adductor longus (or pectineus) and adductor brevis muscles. We injected 20 mL 1% lidocaine containing epinephrine into the interfascial space using a transverse plane approach to make an interfascial injection, not an intramuscular swelling patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
0
14
1
2
Order By: Relevance
“…[12][13][14][15][16] To the best of our knowledge, none of the previous studies of any ultrasound-guided technique, applicable to patients with hip fracture, have investigated the proximal spread of the injectate into the obturator canal and around the obturator nerve branches innervating the hip joint capsule. Furthermore, no studies have investigated spread of injectate to the accessory obturator nerve (AON), which has been reported to innervate the hip joint capsule consistently, when present.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] To the best of our knowledge, none of the previous studies of any ultrasound-guided technique, applicable to patients with hip fracture, have investigated the proximal spread of the injectate into the obturator canal and around the obturator nerve branches innervating the hip joint capsule. Furthermore, no studies have investigated spread of injectate to the accessory obturator nerve (AON), which has been reported to innervate the hip joint capsule consistently, when present.…”
mentioning
confidence: 99%
“…[22][23][24] Moreover, more recent studies reported that the use of an ultrasound in regional anesthesia is associated with higher success rates as 93% to 97.2% in ultrasound-guided ONB procedures. 21,25 Akkaya and colleagues demonstrated a new methodological approach based on a sono-anatomic study to visualize the obturator nerve. They reported patient satisfaction rates as high as 93%.…”
Section: Discussionmentioning
confidence: 99%
“…Bir diğer yaklaşım sadece işaret noktaları kullanılarak yapılan başarı oranı daha düşük olan kör anatomik girişimdir 1 . Son dönemlerde özellikle ultrasonun bölge-sel anestezi pratiğine girmesiyle ultrason eşliğinde yapılan obturator sinir bloğunda daha az komplikasyon ile blok başarı oranının daha çok arttığını bildiren ça-lışmalar vardır (11)(12)(13).…”
Section: Gereç Ve Yöntemunclassified
“…Özellikle sıklığı %10-30 arasında gösterilen aksesuvar obturator sinir bu farkı yaratmış olabilir (12). Ultrason eşliğinde yapılan obturator sinir bloklarının başarısı ise %93 -97,2 arasında değişen oranlarda bildirilmiştir (11)(12)(13). Bu oranlar sinir uyarı-cısı kullanılan bloklara oranla ultrason eşliğinde yapı-lan blokların daha başarılı olduğunu göstermektedir.…”
Section: Bulgularunclassified